State of the Art in European Addictions Nursing: Perspectives From the United Kingdom, Ireland, and the Netherlands. Issue 3 (July 2019) - Clancy, Carmel; Kelly, Peter; Loth, Christien
Abstract : Abstract: In this article, we discuss the state of the art of addiction nursing in Europe. This state is viewed throughout the United Kingdom, Ireland, and the Netherlands and has a direct link to the future. Despite differences, the three countries share nursing values. The start of International Nurses Society in Addictions Nursing Ireland and the Netherlands is only the beginning of a new connection and cooperation Europe-wide.